Empathy Care Training untuk Meningkatkan Perilaku Memaafkan pada Remaja Akhir - Rifka Annisa; Anggia K.E. Marettih (Universitas Islam Indonesia, 2016)
This study aimed to have know influence empathy care training for increase forgiveness on last-adolescense. This research experiment is true experiment use two group pretest-posttest control group design between subject. Subject of the research are 16 last-adolescence which 8 into experiment group and 8 into control group. The data were collected by using forgiveness scale (Nashori, 2012). The result of Mann Whitney U Test analiysis showed value Asymp. Sig. (2 tailed) 0,020 (p<0.05) with value Z score -2.329. It is mean, empathy care training can increase forgiveness to last-adolescense. The result of Wilcoxon Signed Rank Test on experiment group showed value Asymp. Sig. (1 tailed) 0,046 (p<0,05) it is mean there is different at pretest-posttest score. Empathy care training can help last-adolescense increase empathy that so able to describe reflect on position other people guilty also chosen to make a peace with guilty individu and then can increase forgiveness.Â Keyword: forgiveness, empathy care training, last-adolescense.